Pencegahan Kekerasan Seksual dan Anti-Perundungan di Lingkungan Sekolah - Alfonsus Beo Say; Selianza Ramandhani; Theresia Viona Sihombing; Erwin Rasyid; Bondan Wicaksono (North Press, 2025)
This activity was motivated by the increasing number of cases of sexual violence and bullying in schools. To that end, students conducted an educational activity themed “Prevention of Sexual Violence and Anti-Bullying in Schools” at SMPN 86 South Jakarta. The purpose of this activity was to provide students with an understanding of the importance of recognizing, preventing, and reporting acts of violence and bullying from an early age. The methods used in this activity included direct observation, interviews with school officials, and interactive counseling involving seventh-grade students. The results of the activity showed that students became more aware of the forms of violence and bullying and understood the steps to maintain a safe and respectful learning environment. Through this activity, it is hoped that an inclusive, child-friendly, and violence-free school culture will be created.